The Sexual Abuse of Children by Biological Fathers : A Sociological Case Study on Causative Factors, Consequences, and Social Responses within The Family Context - Vindhy Equilla Volvolensza Nova Octaline William; Karen Mwende Kinuthia (Journal of Southern Sociological Studies, 2025)
Sexual abuse of children by biological fathers represents one of the most complex and painful forms of domestic violence, as the perpetrator is a figure who, both socially and symbolically, is expected to be a protector. This study aims to reveal the causative factors, psychosocial impacts, and social responses to sexual abuse committed by biological fathers against their daughters. The research uses a qualitative approach and a case study method, involving in-depth interviews with three survivors. The findings indicate that sexual abuse within the family is heavily influenced by patriarchal structures that normalize male dominance in the household, as well as manipulative and closed patterns of father-child communication. Radical feminist theory is used to explain how patriarchy serves as the root of sexual domination and control over women's bodies, even in private family spaces. Meanwhile, family symbolic theory highlights the breakdown of the father's protective role, which is instead used to silence the victim. The impacts include long-term trauma, social alienation, trust issues, and educational setbacks. Social responses remain inadequate or victim-blaming, while institutional interventions are uneven and lack comprehensiveness. This study recommends child protection reform, gender-equitable family education, and more responsive social empowerment for victims of family-based sexual violence.